Caracterização da distribuição da população: uso de SIGs vs. zoneamento urbano. O estudo de caso de Ituiutaba - MG - Silva, Luis Felipe da (2017)
Geography as a science has your object of study centered on understanding the relationship of society and nature. And among the various topics analyzed, one of the sheds with greater emphasis is studying urban related themes, due to the complexity of the relationship in this medium. Geographical science provides essential tools for the analysis of the elements which highlights the forms and functions. In this context, the research aims to analyze the general urban zoning Ituiutaba-MG and urban growth from the notes contained in the strategic plan and on the zoning, through the use of geographic information systems-Gis and geo-information. Specifically, we sought to: (a) the context of urban planning and zoning specific applied to the urban environment, dissecting his notes and determinations; (b) espacializar the dichotomy that exists in the urban area between urban areas decades of 1970 and 2010, highlighting its features and determinations contained in urban zoning in force in the municipality on the basis of the income of the Census sectors of the municipality and (c) addressed the use and occupation of the soil, as well as your distribution and characterization based on cartographic products generated. Methodologically, the research is structured in phases: initially the operationalization of concepts via bibliographic surveys, related to the concepts of urban geography, urban planning and zoning and the geographical information systems and geoprocessing. the second phase consisted in collecting data, which helped in the understanding of the urban space of Ituiutaba. In the third step, the tabulation of the information available in the digital media, and your subsequent transformation into cartographic materials, which allowed observation and discussion between the premises of zoning and your real application. The municipality of Ituiutaba-MG, once an important granary of Triângulo Mineiro, from 1970 attracted an intense migratory flow thus reaching a significant population for the município and in specific, for your urban area. Thus, the implementation of a strategic plan to sort this out properly measure expansion used to develop the urban environment. However, the stagnation or lack of update of this strategic plan, as well as management of public power little concerned with this issue, the municipality, lost much of the investment potential that received, for other locations nearby. From 2001, it was established the status of cities, which makes a device that goal the urban planning at national level, and in this way in 2006, the municipality of Ituiutaba implements the integrated urban Planning, to enable the orderly development, however no matter how much the city resumes a profile of urban growth, the development itself, little changed. As a final step, analysis in order to understand the areas in the urban area in the municipality, and the impacts of zoning applied to the urban environment.